Refinery feedstocks - Speight, James G. (Boca Raton, FL : Taylor and Francis, 2021)
"Presents a description of the various types of crude oil and also includes a discussion of extra heavy oil and tar sand bitumen. Basic properties and specifications of crude oil and refinery products and their significance in refinery operations are provided"--
Preface. Author. PART 1 Feedstocks - Evaluation and Properties. Chapter 1 Natural Gas, Crude Oil, Heavy Crude Oil, Extra-Heavy Crude Oil, and Tar Sand Bitumen. Chapter 2 Feedstock Evaluation. Chapter 3 Feedstock Composition. Chapter 4 Asphaltene Constituents in Feedstocks. Chapter 5 Instability and Incompatibility. Chapter 6 Introduction to Refining Processes. Chapter 7 Feedstock Chemistry in the Refinery. Chapter 8 Refinery Reactors. PART 2 Feedstocks in the Future Refinery. Chapter 9 Alternate Feedstocks. Chapter 10 Feedstock Integration in the Refinery. Glossary. Conversion Factors. Index.
OCLC-licensed vendor bibliographic record.
Keywords: Petroleum -- Refining; Heavy oil; Oil sands